AN ANALYSIS ON INTERNET-SUPPORTED ENVIRONMENTAL REPORT USING THE APPROACH OF MEDIA RICHNESS THEORY (Study on Mining Companies Registered in BEI) - Ilma, Muhammad Gilang; Sukoharsono, Eko Ganis (Jurnal Ilmiah Mahasiswa FEB, 2014)
Mining industries are business entities that are highly sensitive towards environmental issues. The industries are expected to communicate the corporate environmental information to general stakeholders. The industries use internet as a medium for corporate communication. This study is aimed to  find out the extent of the potentials of the internet utilization as a communication media for environmental report conducted by  public mining companies in Indonesia. The study uses qualitative research method by conducting a media richness theory analysis.  The findings of this study indicate that currently, the potential of the web is not fully  utilised by companies for environmental communication.  Beneficial features of the internet to enhance the quality of corporate environmental communication process are still not been used by companies. Websites are more focused in maximizing internet features to communicate financial information to shareholders. Keywords: Mining, Communication, Environmental, Internet